Considerations on legal remedies in Romanian civil proceedings - Roᶊu, Claudia (Debreceni Jogi Műhely, 2014)
In the system of the Romanian Code of Civil Procedure the legal remedies that can be exercised against judgements are: the appeal, the second appeal, the appeal for legal contest in annulment and review. The appeal is the only ordinary remedy, while all the others are classified as extraordinary remedies. The reasons for which the legal remedies may be exercised vary depending on this qualification, which means that the appeal is applicable for any dissatisfaction of the parties, whereas the second appeal, the legal contest in annulment and the review may be exercised only for reasons explicitly defined by the law. The extraordinary legal remedies cannot be exercised as long as one may lodge an appeal. A legal remedy can be exercised against one judgement only once, if the law provides the same term of exercising the legal remedies for all existing grounds on the date of declaring that specific remedy. The judgement is subject only to the remedies provided by the law, under the respective terms and conditions, regardless of the particulars of its statement of reasons.